THE ROLE OF SALIVARY GLANDS IN ORAL REHABILITATION: FUNCTIONS, IMPORTANCE, PATHOLOGY AND THERAPEUTIC APPROACHES - Kamel Earar; Alina-Ramona Dimofte; Roxana Dragan; Iulia Alecsandra Salcianu; Irina Ruxandra Strambu; Iulian Catalin Bratu; Nicolae Sarbu; Mariana Ilie; Ana Magdalena Bratu; Doriana Agop Forna; Gabi Topor (Romanian Journal of Oral Rehabilitation, 2024)
The salivary glands are essential for oral health, providing not only environments for digestion and taste, but also protection from pathogens. This review examines the functions of salivation, the importance of salivary glands in the context of oral pathology, and therapeutic approaches for their dysfunctions. Pathologies of the salivary glands range from minor conditions, such as sialadenitis, to severe conditions, such as cancer of the salivary glands. These conditions can affect quality of life, the ability to eat and speak, and have systemic implications. Treatment of salivary gland dysfunctions includes pharmacological therapies to stimulate salivary secretion, the use of saliva substitutes, and physical therapies such as ultrasound therapy. Management is aimed at relieving symptoms and improving the function of affected glands. Antioxidant supplements, depending on your circadian rhythm, may help reduce oxidative stress associated with glandular pathologies.